Pemanfaatan Media Edukatif Kartu Tokoh Nasional Berbasis Permainan Card Game dalam Pembelajaran Sejarah Indonesia di SMP - Febrianti, Aurora Nandia; Ciciria, Deri; Saputra, Andika (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
This study aims to determine the utilization of educational media in the form of national hero cards based on card game activities in learning Indonesian History at SMP Negeri 4 Terbanggi Besar. The national hero card media is designed as a learning tool that combines game elements with historical content to increase students' interest, motivation, and engagement in the learning process. The research method used is a descriptive qualitative approach. Data collection techniques include literature study, observation, interviews, and documentation. Data validity was ensured through source triangulation, while data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results indicate that the use of educational national hero card game media is well received by students and teachers, helps students understand the roles and contributions of national figures in Indonesian history, and creates a more active and enjoyable learning atmosphere